Colorimetric image analysis as a factor in assessing the quality of pork ham slices during storage (2015)
ABSTRACT: This study analysed the colour changes of stored pork ham slices at two temperatures (4 and 8°C) to compare two imaging methodologies for estimating colour changes over time in CIELAB colour spaces through a DigiEye® and stereoscope with digital image analysis. Colour space changes were analysed using a computer vision system for image segmentation analysis. It was determined that from the ninth day, changes could be perceived in the representative colour of ham slices using DigiEye®. Finally, colour prediction equations with R 2 >0.85 were determined as a tool for electronic monitoring to assessing the quality of pork ham slices during storage.